(3QSGdI aj Yed GdefGSNGJs - (3CHh GdMSf GdLdGhjs ((3eMeO Hf bGSe Hf eMeO GdYHOdi s)
(3ChdgG (B:s
(3CYde Cf Yed GdefGSNGJ HGdLOhd gh ef GdVGYI GdHOjYg GdYLjHI s
(3BNQgG (B:s
(3ai eYQaI ebOGQ eG dcd hGQK ef CUd GdeSFdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG eSGFd eNJdaIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs